2011
DOI: 10.1164/rccm.201012-1984oc
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Tuberculosis Case Detection via Real-Time Monitoring of Tuberculosis Diagnostic Services

Abstract: Rationale: Tuberculosis case-detection rates are below internationally established targets in high-burden countries. Real-time monitoring and evaluation of adherence to widely endorsed standards of tuberculosis care might facilitate improved case finding. Objectives: To monitor and evaluate the quality of tuberculosis casedetection and management services in a low-income country with a high incidence of tuberculosis. Methods: We prospectively evaluated tuberculosis diagnostic services at five primary health-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 15 publications
3
66
3
Order By: Relevance
“…18,19 In this analysis, we sampled all patients who presented to health centers with cough of more than 2 weeks' duration and underwent sputum examination as part of a TB diagnostic evaluation. We excluded those receiving follow-up monitoring and care for a previous diagnosis of TB.…”
Section: Methodsmentioning
confidence: 99%
“…18,19 In this analysis, we sampled all patients who presented to health centers with cough of more than 2 weeks' duration and underwent sputum examination as part of a TB diagnostic evaluation. We excluded those receiving follow-up monitoring and care for a previous diagnosis of TB.…”
Section: Methodsmentioning
confidence: 99%
“…Two studies included patients who were either smear-or culture-positive. 29,30 In some studies smear positivity was defined as at least 1 25,27,28,30,35,41,42 or at least 2 [22][23][24]34 positive smears, whereas others did not provide any definition. 10,21,26,[31][32][33][36][37][38][39][40] A study from South Africa stratified rates of reported pre-treatment loss to followup by smear status (smear-positive or smear-negative but culture-positive), 23 whereas another study, also from South Africa, reported on pre-treatment loss to follow-up in tuberculosis patients whose diagnosis was established clinically and/ or bacteriologically.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In the remaining 4 studies, patients with a diagnosis of tuberculosis were identified as part of ongoing epidemiological surveillance 30 or were prospectively recruited for follow-up from a chest clinic 33,40 or from primary-health-care centres. 41 The recruitment periods ranged from 3 months 24,34,36 to 90 months. 30 Only 9 studies [22][23][24][25]27,29,31,36,37 applied a cut-off for time since diagnosis -ranging from 1 month to 3 months -to define pretreatment loss to follow-up.…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…(9) Because patients with tuberculosis have contact with other individuals, the World Health Organization recommends prophylaxis in, recording of, and control of those who had direct contact with such patients as a strategy for detecting new cases; this strategy includes the request for tests to investigate contacts. (10,11) Health professionals need to explain clearly how the exam will be done and its importance for the patient and contacts in helping to completely eliminate the disease in the community. (3) Therefore, the professional needs to completely understand the disease, in order the patient trust on his/her guidance.…”
Section: Discussionmentioning
confidence: 99%